Karakteristik Manajemen dan Kepemimpinan Transformasional sebagai Penentu Kreativitas Karyawan yang Dimediasi oleh Kepuasaan Kerja - Joel Faruk Sofyan; Mardina Rianty (Jurnal Maksipreneur, 2023)
Many organizational top managers are increasingly aware of the importance of innovation as a precondition to maintaining sustainable organizational growth. Moreover, creativity is also often seen as the main driving force for innovation. The aim of this study is to analyze the effects of management characteristics represented by the dimensions of supervisor’s humility and abusive supervision, and transformational leadership on employee creativity mediated by employee job satisfaction. Utilizing a purposive sampling method, this study selected 260 back-office employees who work at banks in Indonesia and the online survey was administered during the period of June to July 2022. Employing PLS-SEM as an inferential analysis tool, this study found that a supervisor’s humility and transformational leadership have positive effects, whereas abusive supervision has a negative effect on employees’ job satisfaction. Furthermore, employee job satisfaction was also found to mediate the effects of supervisor’s humility, abusive supervision, and transformational leadership towards employee creativity.